Phin : A Lute of the Isan Region of Thailand - Sinin, Hamdan; Aaliyawani Ezzerin, Sinin; Ezra Alfandy, M. Duin; Khairul Anwar, Mohamad Said; Mawar Suhaila, Ab Razak; Ahmad Faudzi, Musib (North Carolina State University (Department of Wood & Paper Science / College of Natural Resources, Raleigh, NC, USA), 2025)
The phin is a lute that originated in Thailand's Isan region. The strings 1, 2, and 3 for the phin is E4, A3, and E3. It was tuned to the key of G major. The strings 1, 2, and 3 running notes are E4, F4, F4#, G4, A4, B4, C5, D5, E5, F5, G5, A5, B5, C6, D6, and E6; A3, A3#, B3, C4, D4, E4, F4, G4, A4, A4#, C5, D5, E5, F5, G5, and A5; and E3, F3, F3#, G3, A3, B3, C4, D4, E4, F4, G4, A4, B4, C5, and D5, respectively. The keys F4#, B3, and F3# appear in the first octave only from strings 1, 2, and 3, respectively. In this study, the sound was analyzed with a PicoScope oscilloscope and Adobe Audition. The equation for the polynomial (i.e., the fret number versus the partial frequency) for open strings 1, 2, and 3 is ystring1 = 3.14x2 + 9.10x + 316.07, ystring2 = 2.15x2 + 5.51x + 214.55, and ystring3 = 1.51x2 + 6.53x + 146.24. The changes in frequency (the multiplication factor of the x2) increased gradually with the pitch. Strings 3 (E3), 2 (A3), and 1 (E4) showed the multiplication factor of 1.51, 2.15, and 3.14.